Elucidating the primary mechanisms of high-intensity interval training for improved cardiac fitness in obesity - Bo, Bing; Guo, Aijing; Kaila, Severa Jafeth; Hao, Zhe; Zhang, Huiqing; Wei, Jianshe; Yao, Yuan (Frontiers in Physiology, 2023)
Obesity is a global and rising multifactorial pandemic associated with the emergence of several comorbidities that are risk factors for malignant cardiac remodeling and disease. High-intensity interval training (HIIT) has gained considerable attention due to its favorable outcomes of cardiometabolic health in individuals with overweight or obese. The primary aim of this review is to discuss the fundamental processes through which HIIT improves cardiac impairment in individuals with obesity to develop viable treatments for obesity management. In this review, a multiple database search and collection were conducted from the earliest record to January 2013 for studies included the qualitative component of HIIT intervention in humans and animals with overweight/obesity related to cardiac remodeling and fitness. We attempt to integrate the main mechanisms of HIIT in cardiac remolding improvement in obesity into an overall sequential hypothesis. This work focus on the ameliorative effects of HIIT on obesity-induced cardiac remodeling with respect to potential and pleiotropic mechanisms, including adipose distribution, energy metabolism, inflammatory response, insulin resistance, and related risk profiles in obesity. In conclusion, HIIT has been shown to reduce obesity-induced risks of cardiac remodeling, but the long-term effects of HIIT on obesity-induced cardiac injury and disease are presently unknown. Collective understanding highlights numerous specific research that are needed before the safety and effectiveness of HIIT can be confirmed and widely adopted in patient with obesity.